EUROPEAN AND INTERNATIONAL STANDARDS ON MEDICAL DEVICES FOR DENTISTRY. - Jordan Deliversky; Mariela Yaneva-Deliverska; Maya Lyapina; Angelina Kisselova (Journal of IMAB, 2015)
Standards are produced for many different products and services, and may be created for company, national, regional or global application. In Europe there are three different categories of standard: International standard – a standard adopted by an international standardization organization; European standard – a standard adopted by a European standardization body; National standard – a standard adopted by a national standardization body and made available to the public. Harmonized standards play a special role in the EU. A harmonised standard is a European standard elaborated on the basis of a request from the European Commission to a recognised European Standards Organisation to develop a European standard that provides solutions for compliance with a legal provision. Most standards for dental materials have been harmonized through a so-called cumulative standard (EN 1641:2009 - Dentistry - Medical devices for dentistry - Materials). This European Standard specifies general requirements for materials used in the practice of dentistry for the restoration of the form and function of the dentition and which are medical devices. A multiplicity of laws, standards, and recommendations regulate the marketing of medical devices. The medical doctor and the dentist should be informed about the European and international standards concerning medical devices and use only those for which appropriate information is available. The manufacturer/importer is responsible for its products and is potentially liable for damages.